Dialoške razsežnosti empatije pri Edith Stein = Dialogic Dimensions of Empathy at Edith Stein - Simonič, Barbara (Edinost in dialog, 2020)
Empathy is an important mechanism of interpersonal communication and dialo-gue. It could be defined as our ability to feel another person’s feelings and thoughts, and thus gain insight into someone else’s experience. By this we put ourselves in the situation of other, which is the fundamental essence of dialogue - to be human with other human. The ability to understand others has always interested many authors. Among them was Edith Stein (1891-1942), one of the important women who marked the 20th century. She was a recogni-zable philosopher and teacher, born a Jew, and later a Christian and a martyr, and the first Jew born person since the days of the first Church to be canonized. Edith Stein dedicated her doctoral dissertation to empathy, entitled On the Problem of Empathy, and through her later research and way of life revealed what it means to be empathetic and how to live a dialogue with another human being and God. In this paper, we present the fundamental aspects of understanding empathy at Edith Stein and highlight the importance of empathy as a com-petence that is crucial for real, deep and healthy interpersonal relationships and dialogue.